2011
DOI: 10.1007/s11936-011-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Magnetic Resonance Imaging in Posterior Circulation Stroke: Implications for Diagnosis and Prognosis

Abstract: For some time, posterior circulation stroke has been neglected in diagnostic and therapeutic studies for various reasons, such as minor incidence compared to anterior circulation stroke or anatomical and vascular characteristics. This changed at least partly when the New England Medical Center (NEMC) Posterior Circulation Registry was initiated, and now the number of publications concerning posterior circulation stroke is continuously increasing. Whether the differences outweigh the similarities between poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Macroscopic and microscopic anatomy of the posterior circulation differs significantly from the anterior circulation with regard to the supplying vessels (the vertebral arteries (VA) merge and form the single midline basilar artery), the higher frequency of congenital vessel variations (e.g. hypoplasia of the VA, fetal origin of the PCA), and the large variety of supplied anatomical structures (neocortex, allocortex, thalamus, brainstem, and cerebellum)[ 36 ]. Furthermore, differences in the prevalence of atherosclerosis risk factors [ 37 ] as well as differences in pathological changes such as vessel thickening, elastin loss, and concentric intimal thickening [ 38 ] between anterior and posterior circulation have been demonstrated only recently.…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic and microscopic anatomy of the posterior circulation differs significantly from the anterior circulation with regard to the supplying vessels (the vertebral arteries (VA) merge and form the single midline basilar artery), the higher frequency of congenital vessel variations (e.g. hypoplasia of the VA, fetal origin of the PCA), and the large variety of supplied anatomical structures (neocortex, allocortex, thalamus, brainstem, and cerebellum)[ 36 ]. Furthermore, differences in the prevalence of atherosclerosis risk factors [ 37 ] as well as differences in pathological changes such as vessel thickening, elastin loss, and concentric intimal thickening [ 38 ] between anterior and posterior circulation have been demonstrated only recently.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of MRI is in documentation of posterior circulation strokes [13]. Our previous study found that young adults with a posterior circulation infarct were more likely to be misdiagnosed [5].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty to 30% of all ischaemic strokes occur in the territory of the vertebrobasilar (posterior) circulation, including the cerebellum (Bogousslavsky et al, 1993; Flossmann and Rothwell, 2003; Förster et al, 2011; Hong et al, 2009; Khan et al, 2007). Large cerebellar infarcts have traditionally been classified in function of affected arterial perfusion territories (Edlow et al, 2008; Caplan et al, 2005; Marinković et al, 1995; Hartkamp et al, 2013; Tatu et al, 1996), i.e.…”
Section: Introductionmentioning
confidence: 99%